The effects of partner protectiveness and transfer capacity on degree of inter-firm technology transfer in international joint ventures - Abdul Wahab, Sazali; Che Rose, Raduan; Uli, Jegak; Abdullah, Haslinda (Faculty of Economics and Management, Universiti Putra Malaysia, 2010)
Based on the underlying knowledge-based view (KBV) and organizational learning (OL) perspectives, the main objective of this paper is to empirically examine the effects of two critical elements of technology supplier characteristics: partner protectiveness and transfer capacity on two dimensions of degree of technology transfer: degree of tacit and explicit knowledge. Using the quantitative analytical approach, the theoretical model and hypotheses in this study were tested based on empirical data gathered from 128 joint venture companies registered with the Registrar of Companies of Malaysia (ROC). Data obtained from the survey questionnaires were analyzed using the correlation coefficients and multiple linear regression analyses. The results revealed that partner protectiveness, as the critical element of technology recipient characteristics, has 1) a low significant effect on degrees of tacit knowledge, and 2) no significant effect on degree of explicit knowledge. Nonetheless, transfer capacity showed strong significant effects on both degrees of tacit and explicit knowledge; where the effect on degree of explicit knowledge is slightly stronger that its effect on degree of tacit knowledge. The study has bridged the literature gaps in such that it offers empirical evidence on the effects of two generic technology supplier attributes: partner protectiveness and transfer capacity on degree of inter-firm technology transfer: degree of tacit and explicit knowledge in IJVs.